A Native Growing Season Forage for Wildlife - Teaweed, Sida acuta Burm. f. - Rick Williams; Tim Baxley (EDIS, 2007)
FOR-114, a 4-page illustrated fact sheet by Rick Williams and Tim Baxley, describes this shrub, also known as ironweed or southern side, that, although it is a problem for agriculture, makes a good wildlife forage for white-tailed deer and other native wildlife. Includes sections on plant characteristics, benefits and management; includes references. Published by the UF School of Forest Resources and Conservation, December 2006.